Penerapan Strategi Pembelajaran berbasis Aplikasi Deutsche Welle Learn German Terhadap Keterampilan Menyimak (Hören) dan Berbicara (Sprechen) bagi Mahasiswa - Angreany, Femmy; Syaputra, Arlian Fachrul (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
The purpose of this study was to investigate the effectiveness of Deutsche Welle Learn German as as strategy in the teaching of German listening (Hören) and speaking (Sprechen) skills. This study used a pre experimental method with a one-grup pre-test and post -test design during 6 meetings. The analysis of students performance before and after the implementation of the application using descriptive statistics and inferential statistic. Descriptive statistics aimed to describe the level of students performance. While inferential statistic aimed to determine whether the significant effect of DW Learn German medien listening and speaking skills of second-semester student in the German Language Education. Results show that learning strategy through Deutsche Welle Learn German application was effective and significantly improved the listening and speaking skills of second-semester student in the German Language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Makassar.